2018
DOI: 10.1017/s0142716418000048
|View full text |Cite
|
Sign up to set email alerts
|

Predicting sign learning in hearing adults: The role of perceptual-motor (and phonological?) processes

Abstract: The present study aimed to identify predictors of one aspect of sign language acquisition, sign learning, in hearing nonsigners. Candidate predictors were selected based on the theory that the observed relationship between phonological short-term memory and L2 lexical learning is due in part to common perceptual-motor processes. Hearing nonsigning adults completed a sign learning task, three assessments of short-term memory for movements (movement STM; two of which used sign-like stimuli), and two visuospatial… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 90 publications
(128 reference statements)
2
19
2
Order By: Relevance
“…In the NSPT, participants must judge whether target pseudosigns differ from their reproductions (see Figure 5). Martinez and Singleton (2018) observed moderate to strong correlations between it, a sign learning task, two visuospatial STM tasks, and another putative task of signed-PSTM, the Nonsign Repetition Task (Mann et al, 2010), providing evidence of the validity of the NSPT as a measure of signed-PSTM.…”
Section: Nonsign Paired Task (Nspt)mentioning
confidence: 85%
See 4 more Smart Citations
“…In the NSPT, participants must judge whether target pseudosigns differ from their reproductions (see Figure 5). Martinez and Singleton (2018) observed moderate to strong correlations between it, a sign learning task, two visuospatial STM tasks, and another putative task of signed-PSTM, the Nonsign Repetition Task (Mann et al, 2010), providing evidence of the validity of the NSPT as a measure of signed-PSTM.…”
Section: Nonsign Paired Task (Nspt)mentioning
confidence: 85%
“…Thus, in ASL, APPLE and CANDY are minimal pairs (lexical items that differ by one phoneme; for an English example, consider rat and bat). At least one study has found that signed-PSTM tasks, utilizing sign-like material, are related to sign learning (Martinez & Singleton, 2018). Given the scarcity of research investigating signed-PSTM and sign learning, it is also worth noting that signed-PSTM tasks are related to other language outcomes in deaf children who sign (Marshall et al, 2015;Mason et al, 2010) as well as in hearing sign language interpreters (Gómez, Molina, Benítez, & de Torres, 2007;Shaw, 2011)-relationships that are analogous to those observed in spoken language research (Daneman & Merikle, 1996;Gathercole & Baddeley, 1990).…”
Section: Phonological Short-term Memory In Signed and Spoken Languagesmentioning
confidence: 99%
See 3 more Smart Citations